Problem-based learning in social studies cues to culture and change - Moye, Valerie Hastings (Shoebox curriculum)
Pick up Problem-Based Learning in Social Studies: Cues for Culture and Change and find out just how easy it is to integrate the essential life skill of problem solving into the curriculum. This sourcebook focuses on two key concepts of problem-based learning: culture and change. It then defines ten big ideas of culture and change, which form the basis for five learning objectives outlining the goals for the learner. Complete with more than 25 activities and numerous assessments and blacklines, the ideas and learning experiences, in the form of activities, can be easily adapted for K-College classrooms. Take advantage of Problem-Based Learning in Social Studies: Cues for Culture and Change and create mind-opening problem-solving opportunities across the curriculum.